2012
DOI: 10.1080/15332586.2012.720175
|View full text |Cite
|
Sign up to set email alerts
|

Lethality Assessments and the Law Enforcement Response to Domestic Violence

Abstract: More and more police departments are adopting lethality assessment programs (LAPs), requiring police officers responding to an incident of intimate partner violence to assess with victims their risk for death at the hands of their abusers. In this study, the author explores the initial enthusiasm for these programs and claims of dramatic drops in homicides. He questions whether, like previously hailed criminal justice responses to intimate partner violence, LAPs will be found to offer only incremental improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The extensive literature on the subject of DV has created a context for social policy initiatives as they attempt to tackle this pervasive societal issue (Messing et al, 2016). Moreover, while it is obvious DV needs to be addressed at all levels of society, none may be more important than the role of the responding police officer (Klein, 2012). The early trends of the 1980s showed that the arrest of an abuser significantly reduced repeated incidents of abuse, compared to interventions using medication and counseling (Radatz & Wright, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The extensive literature on the subject of DV has created a context for social policy initiatives as they attempt to tackle this pervasive societal issue (Messing et al, 2016). Moreover, while it is obvious DV needs to be addressed at all levels of society, none may be more important than the role of the responding police officer (Klein, 2012). The early trends of the 1980s showed that the arrest of an abuser significantly reduced repeated incidents of abuse, compared to interventions using medication and counseling (Radatz & Wright, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adoption of lethality assessment programs is on the rise in police departments (as of 2015, jurisdictions in 34 states are implementing the LAP), requiring police officers responding to an incident of IPV to work with the victims to determine their risk for death (Klein, 2012). The program implemented in the state of Connecticut is a result of a collaboration between the Connecticut Coalition Against Domestic Violence [CCADV] and the Connecticut Police Officer Standards and Training Council (POSTC).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While some scholars promote external assessments such as the LAP as tools that assist service providers and victims alike in recognizing the seriousness of domestic violence (e.g., Campbell, 2005; Goodman, Dutton, & Bennett, 2000), others have taken a more critical approach considering appropriateness, victims’ own self-assessment, and the potential impact on victim empowerment and autonomy (Hoyle, 2008; Johnson, 2010; Klein, 2012; Websdale & Dedolph, 2000). Furthermore, the implementation of these tools has outpaced comprehensive empirical evaluation research.…”
Section: Introductionmentioning
confidence: 99%